Mapping and analysis of socio-spatial inequalities: interpretative approach from the city of Belém, Pará - Vieira, Denise Carla de Melo; Rodrigues, Jondison Cardoso; Rodrigues, Jovenildo Cardoso (Geosaberes; Vol 9 No 17 (2018): Jan - AprDO - 10.26895/geosaberes.v9i17.612, 2017)
The spaces embodied in the logics of capitalist production tend to produce more and more masks and repetitions, as general syntheses that express contradictions and ambivalences, constituting a condition for the reproduction of differentiations and socio-spatial inequalities (SSI). In this sense, the article aims to map and analyze the SSI, based on an interpretive approach on household income in the city of Belém, in Pará state. Data were used on IBGE census tracts, cartographic production and systematic observation. The worst indicators based on income are concentrated in the Northeast. The concentrations of the highest incomes are located in the Central, South and Southwest regions. It was verified that two districts that are registered in the "periphery" areas have high income, mainly because of horizontal condominiums.
Keywords: Desigualdades Socioespacial, diferenciações socioespaciais, Belém